PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI CANVA MATERI NORMA DAN ADAT ISTIADAT DAERAHKU KELAS IV SD NEGERI 72 PALEMBANG - Ramadani, Tri Novita Sapar; Puspita, Yenny; Oktavia, Maharani (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of this research is to develop interactive learning media based on the Canva application for the topic of norms and customs at fourth grade of elementary school. The study applied the ADDIE research and development model, which consists of five development steps: analysis, design, development, implementation, and evaluation. The subjects for the trial were 31student of fourth-grade from SD Negeri 72 Palembang. The research results in the development of interactive learning media based on the Canva application which is valid, practical, and effective. The validation percentage was 88%, the practicality percentage based on student responses was 89%, and the effectiveness percentage was 93%, indicating that the media is highly suitable to be used.